Ketersediaan Hara Fosfor dan Logam Berat Kadmium Pada Tanah Ultisol Akibat Pemberian Fosfat Alam dan Pupuk Kandang Kambing Serta Pengaruhnya Terhadap Pertumbuhan dan Produksi Tanaman Jagung (Zea mays L.) - Jona Simanjuntak; Hamidah Hanum; Abd Rauf (Jurnal Agroekoteknologi, 2015)
Studies on the availability of nutrients phosphorus and heavy metals cadmium on Ultisol fromapplication of natural phosphate and goat manure on the growth and production of maize (Zea maysL.) has been implemented in the Experimental Farm, Faculty of Agriculture University of NorthSumatra, Medan since April to by October 2014. this study aims to determine the availability ofnutrients phosphorus and heavy metals cadmium on Ultisol from application of natural phosphateand goat manure on the growth and production of maize. The method uses random sampling studygroup (RAK) factorial consisting of two factors: natural phosphate (0 ppm, 75 ppm, 150 ppm, and225 ppm) and goat manure (0 tons / ha, 10 tons / ha, 20 tons / ha, and 30 tons / ha). The resultsshowed that administration of natural phosphate significantly in improving P-available, plant Puptake, growth, and yield of corn in a linear manner. Goat manure significant effect in increasingthe pH, available P, P uptake of plants, growth, and yield of corn in a linear manner. Interaction ofphosphate and goat manure significantly in improving crop P uptake and the best combination is anatural phosphate 75 ppm and goat manure 30 tons / ha.. Cd content of the soil result to theapplication of rock phosphate 75 ppm - 225 ppm and goat manure 10 tons / ha - 30 tons / ha, are notincluded in the dangerous category.Keywords: rock phosphate, goat manure, cadmium, phosphate, corn